Electrochemical–Thermal Evaluation of an Integrated Thermal Management System for Lithium‐Ion Battery Modules. Issue 6 (30th April 2018) - Bahiraei, Farid; Ghalkhani, Maryam; Fartaj, Amir; Nazri, Gholam‐Abbas
Abstract: Thermal management of lithium‐ion (Li‐ion) batteries using phase change materials (PCM) demonstrate advantages such as compactness and reduced weight compared to conventional active cooling systems. However, the heat accumulation in PCM due to ineffective cooling and added thermal inertia may lead to thermal management system failure. In this study, a hybrid active–passive thermal management system for a Li‐ion battery module is presented. Graphite nanopowder and highly oriented pyrolytic graphite sheets are employed to improve the low thermal conductivity of the PCM. The thermophysical properties of the nano‐enhanced PCM (NePCM) with various mass fractions are experimentally explored. A streamlined electrochemical–thermal coupled model for batteries is used to develop an air‐assisted hybrid thermal management system model. The effects of nanoparticles mass fraction, thickness of the PCM layer, and air inlet temperature on the module thermal behavior during a standard driving cycle are investigated. The hybrid system can maintain the module temperature within the safe limits and provide excellent temperature uniformity. The results reveal that an enhanced thermal conductivity is essential to recover the thermal energy storage capacity of PCM during the driving cycle. The proposed cooling approach presents a promising avenue for enhanced thermal management of Li‐ion battery modules. Abstract : Thermal management of lithium‐ion batteries (Li‐ion) using phase change materials demonstrates advantages such as compactness and reduced weight compared to conventional active cooling systems. In this study, a hybrid active–passive thermal management system for a Li‐ion battery module is presented. The proposed cooling approach presents a promising avenue for enhanced thermal management of Li‐ion battery modules.